2007
DOI: 10.1111/j.1467-8624.2007.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

An ERP Study of Emotional Face Processing in the Adult and Infant Brain

Abstract: To examine the ontogeny of emotional face processing, event-related potentials (ERPs) were recorded from adults and 7-month-old infants while viewing pictures of fearful, happy, and neutral faces. Face-sensitive ERPs at occipital-temporal scalp regions differentiated between fearful and neutral/happy faces in both adults (N170 was larger for fear) and infants (P400 was larger for fear). Behavioral measures showed no overt attentional bias toward fearful faces in adults, but in infants, the duration of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
278
12
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 292 publications
(334 citation statements)
references
References 62 publications
(110 reference statements)
39
278
12
5
Order By: Relevance
“…This is in contrast to prior ERP work with infants using face stimuli presented above the perceptual threshold (for at least 500 ms) that found a larger Nc for fearful than for happy faces (38,39). This discrepancy might be related to methodological differences across studies concerning the duration of presentation (subliminal, supraliminal), the nature of the stimulus (face, eyes), or a combination of the two.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This is in contrast to prior ERP work with infants using face stimuli presented above the perceptual threshold (for at least 500 ms) that found a larger Nc for fearful than for happy faces (38,39). This discrepancy might be related to methodological differences across studies concerning the duration of presentation (subliminal, supraliminal), the nature of the stimulus (face, eyes), or a combination of the two.…”
Section: Discussioncontrasting
confidence: 53%
“…However, it is not until the age of 7 mo that they show a robust attentional bias to fear, as reflected in their neural and behavioral responses (37)(38)(39)(40)(41). The developmental emergence of this fear bias has been linked to the maturation of frontolimbic circuits (42)(43)(44)(45) and occurs at a point in development when infants begin to first experience fear themselves (46,47).…”
Section: Significancementioning
confidence: 99%
“…Indeed, the late stages of pregnancy (Pearson, Lightman, & Evans, 2009;Roos et al, 2012) and increased OT levels following intranasal OT administration (Van IJzendoorn & Bakermans-Kranenburg, 2012) are associated with increased sensitivity to adults' facial expressions, suggesting a generalized bias. To address the infant specificity, we measured responses also to adults' fearful and happy expressions which have been consistently associated with distinct ERP effects (i.e., larger responses to fearful vs. happy faces; Batty & Taylor, 2003;Leppänen, Moulson, Vogel-Farley, & Nelson, 2007). EEG was recorded while mothers and non-mothers were MOTHERHOOD, OXTR, AND INFANT FACIAL EXPRESSIONS 5 presented with a stream of infant and adult facial expression stimuli.…”
Section: Motherhood Oxtr and Infant Facial Expressionsmentioning
confidence: 99%
“…Electroencephalography (EEG) and magnetoencephalography (MEG) studies have provided mixed results regarding the speed of processing in the subcortical system, with some studies showing fast processing of emotional stimuli before any fine-grained analysis or attentional modulation can occur 98,99 , and others showing longer latencies 100 . A recent study that combined MEG and MRI methods reported early, event-related synchronization in the posterior thalamus (probably in the pulvinar), as fast as 10-20 ms after onset of the presentation of fearful facial expressions, followed by eventrelated synchronization in the amygdala at 20-30 ms after onset 101 .…”
Section: Comparing Attentional and Sensory Unawarenessmentioning
confidence: 99%